If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 5 + 6z = 0 Solving 5 + 6z = 0 Solving for variable 'z'. Move all terms containing z to the left, all other terms to the right. Add '-5' to each side of the equation. 5 + -5 + 6z = 0 + -5 Combine like terms: 5 + -5 = 0 0 + 6z = 0 + -5 6z = 0 + -5 Combine like terms: 0 + -5 = -5 6z = -5 Divide each side by '6'. z = -0.8333333333 Simplifying z = -0.8333333333
| x/5=17 | | .25(y-b)=m | | 3t+5=-15 | | 5-2x=3+3x-4x | | 8x+10-(2x+5)=-55 | | -2(m-60)=-m | | 5m=3m+6 | | 9x=2x^2-18 | | 8x-12=15x+10 | | 6x+12=-6 | | 4+p^2+12p=0 | | 2(x-3)=x+9 | | X^2+7x-38=0 | | x^2+50x+336=0 | | 4x+12=-2(x-3) | | -3(2x-1)=4-3x | | x^2-8x-1008=0 | | s-31=20.6 | | 6x+2=8x-2 | | x^2-4x-320=0 | | 7.2+c=19 | | 25(y+1)-x^2(y+1)= | | -2x-1=0 | | x^2+43x+432=0 | | x+0.08x=4.32 | | 6a+10=4a+16 | | r^2+5r+4= | | 2x+2=7x-2 | | (3x^2-7x-6)+(-3x+2)= | | 8x^2-14x+3= | | 4(2c+3)7=13 | | 456=-130r-60r |